ON M-Projectively Flat LP-Sasakian Manifolds - Zengin, F. Ö. (Ukrains’kyi Matematychnyi Zhurnal, 2013)
In the present paper, we study the nature of LP-Sasakian manifolds admitting the M-projective curvature tensor. It is examined whether this manifold satisfies the condition W(X, Y ).R = 0. Moreover, it is proved that, in the M-projectively flat LP-Sasakian manifolds, the conditions R(X, Y ).R = 0 and R(X, Y ).S = 0 are satisfied. In the last part of the paper, an M-projectively flat space-time is introduced, and some properties of this space are obtained.